Democracy Mirror: Voter Participation Increasing or Decreasing? The case of the 2020 Pandeglang Regional Election in the Middle of Covid 19 - Jeni - Minan (Administrative Law and Governance Journal, 2021)
This paper discusses the increase or decrease in voter participation in Pandeglang Regency in the 2020 Pemilukada amid the exposure to Covid-19, as a reflection of the essence of democracy in Indonesia. The approach used in this paper is qualitative, with descriptive analysis techniques. The results of the discussion concluded that the electoral participation in Pandeglang Regency in the Regional Head General Election of December 9, 2020, increased even though it did not match the figures targeted by the Pandeglang KPU. This assessment is considering its implementation in the middle of Covid-19 and the floods that hit Pandeglang. Also the figures achieved were higher than the achievements of the previous regional head elections in 2015.